Correlation between Some of Pitx2 Snps with Milk Production and Contents in Goat - Al-Rubaye, Shaimaa G. A.; Nayef , Inaam Abdul Wahed (American Journal of Botany and Bioengineering, 2025)
The study was conducted at the ruminant research station of the Agricultural Research Department / Ministry of Agriculture for the period from 1-1 2022 to 4-3 2022 for the purpose of determining the single nucleolide polymnorphisms (SNPs) of the Paired like homoedomain transcription factor 2 gene and milk production. 52 A goat under the same rearing conditions (16 local goats and 36 Shami goats). The results of the current study showed the emergence of four mutations in the operating region of the gene, according to the DNA sequencing method. The size of the studied plot 966 base pairs resulted in the mutations G1148A and G1089A, which resulted in two genotypes: wild GG and hybrid GA with the absence of the AA mutant, while three different genotypes emerged at the mutation C1141A and they were wild CC, CT hybrid, TT mutant, and the mutation G1003A emerged from them. Structures, wild, hybrid and mutant GA, GG, AA. The difference of the strain had a significant effect (05.P < 0) on the length of the milk season, the rate of daily milk production and the percentage of protein in the milk. The total milk production rate was not affected in addition to the percentages of fat, lactose and solids in the milk. The percentage of protein in milk differed according to the genotypes within the G1148A mutation. The G1089A mutation caused a variance in the length of the milk season, the daily and total milk production rate, and the percentage of fat in that the wild formula GG was superior to the values of these traits than the GA compound. The G1003A mutation was significant in the length of the milk season with the ratios of both protein and fat in milk (05.P < 0). The Shami goats outperform the local ones in the length of the milk season, the total milk production rate and the protein content in the milk, which reached 65.198 days, 78.317 kg and 77.2% for the local one. The GG wild model was higher in the protein content in the milk 95.2%, while it reached 71.2% for the GA hybrid. Within the G1148A mutation. About the G1089A mutation, individuals carrying the wild formula GG recorded the highest measurements of the length of the milk season and the average daily and total milk production, which were 89.194 days, 37.350 g and 28.68 kg, in addition to the percentage of fat in milk 58.2%. The G1003A mutation produced the highest longest seasonal milk, which is 50,221 days for the mutant AA. As for the milk content of protein and fat, it was 12.3% and 61.3% higher than that of the wild and hybrid formulations.